PERANCANGAN SISTEM UKURAN KEMEJA ANAK-ANAK INDONESIA DENGAN MENGGUNAKAN K-MEANS CLUSTERING DAN METODE ELBOW - Novenda Kartika Putrianto; Yehezkiel San Darrel Erbi Saputra (KAIZEN : Management Systems & Industrial Engineering Journal, 2022)
Clothes are divided into two types: custom and ready-to-wear (RTW). RTW is available in stores in a wide selection of sizes. However, the size of each brand can be different. Therefore we need a standard that regulates the size of clothes. Indonesia already has SNI 7929:2013 and SNI 7930:2013 which regulates the size of shirts for boys and girls. However, both SNIs still have drawbacks. This study aims to provide a design proposal that can be adopted by Indonesia manufacturers. The data taken are anthropometric data of 222 boys and 200 girls with 16 variables. The elbow method is used to get the optimal number of sizes and the k-means clustering is used to obtain the shirt size. The results showed seven size charts can be used as a reference as the evaluation of the aggregate loss and cover factor analysis has been met.